Neighbourhood environment and the effect on well-being, physical activity, and social connectedness : a thesis presented in partial fulfilment of the requirements for the degree of Masters of Science in Psychology, Massey University, Palmerston North, New Zealand - Anderson, Jesse (Massey University, 2021)
The world's population is ageing. Efforts are being made to improve health outcomes for these ageing populations. There has been a shift from the medical model of health (personal responsibility) to an Active Ageing model, which can be defined as holistic, enlisting organisational, societal, and individual action to support better health and well-being outcomes. Governments are well-placed to play a more significant role in improving public health by contributing to the social and environmental determinants of health. The Capabilities Approach is a useful framework with which to consider the environmental impact on health, with well-being as the defining subjective measure of an individual's health. According to the Capabilities Approach, well-being is positively affected via achieved functionings. The Capabilities Approach recognises the role of external support in achieving positive health outcomes. The residential neighbourhood environment is one external factor associated with health and well-being. It is also amenable to positive interventions to support improved health and well-being outcomes for individuals. There are many ways to conceptualise and measure external, residential neighbourhood environments. This study included objective, subjective and socio-economic measures of the local neighbourhood environment. Objective measures of the environment capture natural and built elements. Subjective measures of the environment capture residents' feelings towards their local neighbourhood, such as safety and trust. Socio-economic measures (SES) of the environment provide demographic information about the population's income, education and household composition. This study examined the relationship between these environmental measurements and well-being. It was hypothesised that people who live in neighbourhoods which scored higher on environmental measures would have higher self-reported well-being levels. Environmental data was collected using self-reported environment measures, objective environmental measures (OPERAT) and socio-economic measures from Australian Bureau of Statistics census data (SES). Two pathways which may explain this relationship between the residential neighbourhood environment and well-being were examined: physical activity (a physical health construct) and social connectedness (a mental health construct). Participants were selected from three, social disparate SES groups (high, medium and low) and survey data was collected by questionnaire related to their perceptions of the local neighbourhood environment, self-reported physical activity, social connectedness and well-being. Objective environmental measures were taken by the researcher utilising OPERAT for each area. The environment was found to be significantly related to self-reported well-being across all measures (self-reported, objective and SES). The relationship between environment and well-being was more significant for older people. Physical activity was found to mediate the relationship between the perceived quality of the neighbourhood environment and well-being. SES was found to be more strongly related to well-being and subjective perceptions of the local neighbourhood environment at lower levels of SES. Objective measures of the neighbourhood identified a significant relationship with measures of Subjective Environment and Well-being for older people. Overall, the research findings suggested the use of multiple measures of the local neighbourhood environment to measure effects on well-being. Future research could be undertaken to understand further the relative contribution each type of environment makes, especially for older people, towards well-being, and the pathways by which this is achieved. Such research would be invaluable in regard to efficient decision making associated with the effective allocation of resources to improve health outcomes.
Keywords: 520304 Health psychology